2019
DOI: 10.1186/s13104-019-4826-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Streptococcus suis from sick pigs in Bali, Indonesia

Abstract: ObjectiveStreptococcus suis (S. suis) is a causative agent for various syndromes in pigs. It can be transmitted to humans with typical symptoms of meningitis and death. Although human infections have been confirmed at Bali Referral Hospital, Indonesia, since 2014, the bacteria have not been isolated from pigs. Here, we provide confirmation of the presence of the bacteria in sick pigs in the province.ResultsStreptococcus suis was confirmed in 8 of 30 cases. The final confirmation was made using PCR and sequenci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The detection level varies from 5 to 40%, depending on the presence of clinical signs [ 26 ]. Our results, together with those of a previous study [ 9 ], indicate that S. suis seems to be enzootic in Bali; this possibility needs to be investigated. Biosecurity in small-scale pig farming needs to be promoted, and regular sampling in slaughterhouses needs to be conducted to improve sanitary measures.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The detection level varies from 5 to 40%, depending on the presence of clinical signs [ 26 ]. Our results, together with those of a previous study [ 9 ], indicate that S. suis seems to be enzootic in Bali; this possibility needs to be investigated. Biosecurity in small-scale pig farming needs to be promoted, and regular sampling in slaughterhouses needs to be conducted to improve sanitary measures.…”
Section: Discussionsupporting
confidence: 69%
“…At Bali Provincial Sanglah Hospital, 71 patients had suspected bacterial meningitis between August 2014 and December 2017 and 44 were confirmed to have S. suis infections [ 8 ]. The wide spreading of the bacteria in pigs in the province has been confirmed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most serotypes caused suppurative lesions, meaning that neutrophils accumulated in the organs and formed pus. Since then, neutrophils in the lesions were characterized in various swine studies [9,129,130]. In mouse models, neutrophils also infiltrate both systemic [101,[131][132][133][134][135][136] and brain lesions [7,137].…”
Section: S Suis-induced Lesions Contain High Infiltration Of Neutrophilsmentioning
confidence: 99%
“…A S. suis isolate from field cases of sick pigs and confirmed to be serotype 2 or ½ designated PPB5 (Besung et al 2019) were used in this study. The isolate was aliquoted and preserved in a deep freezer (-80°C) with 10% glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental infection of Streptococcus suis isolate in pig in Bali -Indonesia produced mild clinical signs but severe multiorgan lesions. International Journal of Veterinary Science 12(3): 443-449. https://doi.org/10.47278/journal.ijvs/2022.214 during August 2014 and December 2017 (Susilawathi et al 2019), although the bacteria has been confirmed to be widely spread in pigs in that province (Besung et al 2019). A large cluster of zoonotic transmission of S. suis in the province that has been reported (Tarini et al 2022) is considered unusual trough sharing common source of infected traditional food.…”
Section: Introductionmentioning
confidence: 99%